(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: In the pathobiology of neurodegenerative diseases (NDDs), including Huntington’s, Parkinson’s, and Alzheimer’s, epigenetic dysregulation has become a significant factor. Neuronal dysfunction and degeneration have been linked to dysregulated non-coding RNAs, aberrant DNA methylation, and histone changes. Environmental pollutants, which cause oxidative stress, inflammation, and genomic instability, frequently make these changes worse. Reversing epigenetic abnormalities might provide a way to mitigate neurodegeneration and restore brain systems. Objective: To synthesize current knowledge on the epigenetic mechanism”, “Epigenetic Alterations in Neurodegenerative Diseases”, “epigenetic therapy in neurodegeneration”, and challenges, limitations in epigenetics of neurodegenerative disorders. Methodology: A narrative review was conducted through a structured search of PubMed, Scopus, Web of Science, and Google Scholar, focusing on articles published on role of epigenetic landscape of Neurodegenerative Diseases and Its Therapeutic Potential. Keywords related to epigenetic mechanism”, “Epigenetic Alterations in Neurodegenerative Disorders”, “epigenetic therapy in neurodegeneration”, and challenges, limitations in epigenetics of neurodegenerative disorders. Results: The review emphasizes the critical role of epigenetic landscape of neurodegenerative diseases and its therapeutic potential in the wide range. It identifies A revolutionary strategy for tackling the underlying mechanisms of NDDs is the use of epigenetic modulators. These treatments have the ability to reverse the epigenetic dysregulation brought on by environmental pollutants and genetic predispositions by focusing on reversible alterations in gene expression. Conclusion: As the concluded remarks a revolutionary strategy for tackling the underlying mechanisms of NDDs is the use of epigenetic modulators.